The effects of simple febrile seizure on apoptosis molecular alterations in hippocampus of rat neonates - Mohamad Javad Saeedi-Boroujeni; Ghasem Sazegar; Javad Hami (Journal of Rehabilitation, 2013)
Objective: Febrile seizures are the most common seizure disorder in childhood, and occur in 2-5% of children. While simple febrile seizures are frequently described as inoffensive disorder there are evidence suggesting the association between simple febrile seizures and hippocampal abnormalities in adulthood. This study was designed to evaluate the protein levels of Bcl-2 and Bax in the rat neonates’ hippocampus due to Simple Febrile Seizure.